Myeloid cell TBK1 restricts inflammatory responses - Gao, Tianxiao; Liu, Ting; Ko, Chun-Jung; Zhang, Lingyun; Joo, Donghyun; Xie, Xiaoping; Zhu, Lele; Li, Yanchuan; Cheng, Xuhong; Sun, Shao-Cong (Proceedings of the National Academy of Sciences - PNAS, 2022)
Proinflammatory cytokine production by innate immune cells plays a crucial role in inflammatory diseases, but the molecular mechanisms controlling the inflammatory responses are poorly understood. Here, we show that TANK-binding kinase 1 (TBK1) serves as a vital regulator of proinflammatory macrophage function and protects against tissue inflammation. Myeloid cell–conditional Tbk1 knockout (MKO) mice spontaneously developed adipose hypertrophy and metabolic disorders at old ages, associated with increased adipose tissue M1 macrophage infiltration and proinflammatory cytokine expression. When fed with a high-fat diet, the Tbk1-MKO mice also displayed exacerbated hepatic inflammation and insulin resistance, developing symptoms of nonalcoholic steatohepatitis. Furthermore, myeloid cell–specific TBK1 ablation exacerbates inflammation in experimental colitis. Mechanistically, TBK1 functions in macrophages to suppress the NF-κB and MAP kinase signaling pathways and thus attenuate induction of proinflammatory cytokines, particularly IL-1β. Ablation of IL-1 receptor 1 (IL-1R1) eliminates the inflammatory symptoms of Tbk1-MKO mice. These results establish TBK1 as a pivotal anti-inflammatory mediator that restricts inflammation in different disease models.